1997
DOI: 10.1007/s004150050118
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis due to viridans streptococci in adults

Abstract: Seven patients are reported with meningitis due to viridans streptococci. These patients represented 5% of culture-proven cases of bacterial meningitis in adults participating in a prospective multicentre clinical trial evaluating the use of dexamethasone. Meningitis was iatrogenic in three patients: one patient had been treated with endoscopic sclerotherapy for oesophageal varices, and two patients had undergone thermocoagulation of the gasserian ganglion for trigeminal neuralgia in the previous days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 9 publications
0
26
0
1
Order By: Relevance
“…In addition to the case reported here, there were 11 cases related to a leak of CSF. Of these leak-related cases, five developed following head trauma, 7,10,35,39 two cases were complications from a neurosurgical procedure, 20,27 two were due to spontaneous dural defects, 22,29 one was due to a sphenoid mucocele, 34 and a single case was associated with chronic sinusitis and otitis media (like our patient). 30 The remaining cases (5 of 57) were associated with possible translocation from the gastrointestinal tract.…”
Section: Exposure/inoculationmentioning
confidence: 61%
See 1 more Smart Citation
“…In addition to the case reported here, there were 11 cases related to a leak of CSF. Of these leak-related cases, five developed following head trauma, 7,10,35,39 two cases were complications from a neurosurgical procedure, 20,27 two were due to spontaneous dural defects, 22,29 one was due to a sphenoid mucocele, 34 and a single case was associated with chronic sinusitis and otitis media (like our patient). 30 The remaining cases (5 of 57) were associated with possible translocation from the gastrointestinal tract.…”
Section: Exposure/inoculationmentioning
confidence: 61%
“…She underwent operative endoscopic evaluation, and two defects were found. A defect in the planum sphenoidale measured approximately 3 mm and was CM&R 2012 : 1 (February) 22 S. salivarius meningitis repaired using a free mucosal graft. Another large linear defect was noted in the left cribiform overlying the olfactory tube, measuring about 1 cm by 3 mm.…”
Section: Csfmentioning
confidence: 99%
“…Bacterial meningitis caused by viridians streptococcus was once presumed to be rare; however, several authors have now reported the prevalence of viridians streptococcus meningitis to not be so uncommon, accounting for 5-9% of all cases of bacterial meningitis (3)(4)(5). Furthermore, it appears to be an increasing cause of hospital-acquired meningitis and accounts for 5% of cases of nosocomial meningitis in adults (2).…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with meningitis caused by viridians streptococcus are reported to have underlying conditions such as infectious endocarditis, head trauma, gastroenteritis or sinusitis or to have previously undergone neurosurgical procedures (6). Several studies have reported that posttraumatic and/or post-neurosurgical states and medical procedures are major risk factors for viridians streptococcus meningitis (2,4). Therefore, with further advances in medicine, the number of cases of streptococcus meningitis is expected to increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation